The Neurological Hand Deformity Classification for children with cerebral palsy - Georgiades, M.; Elliott, Catherine; Wilton, J.; Blair, E.; Blackmore, M.; Garbellini, S. (Wiley-Blackwell Publishing Asia, 2014)
Background/aim: The purpose of this study was to evaluate the reliability of the Neurological Hand Deformity Classification and use it to describe changes in hand deformity over time in children with cerebral palsy. Methods: We identified 114 video clips of 26 children with cerebral palsy, aged 1–18 years (mean = 8.4, SD = 4.2), performing upper-limb tasks at multiple time points (n = 3–8) at least 6 months apart. Using the Neurological Hand Deformity Classification, three observers classified hand deformity in the video clips. Inter- and intra-observer reliabilities were estimated using Fleiss and Cohen's kappa (κ) and the temporal changes in classification of hand deformity were investigated. Results: Inter- and intra-observer reliability respectively were κ = 0.87 and κ = 0.91. Hand deformity was identified in all children at all-time points, even before the age of 2 years. Ten children did not change hand classification, wrist flexion increased in eight and eight showed changes from wrist flexion to extension or vice versa. Conclusions: The Neurological Hand Deformity Classification is a reliable tool to classify hand deformity in children with cerebral palsy. For more than one-third of children hand deformity classification did not change. For the remaining children, two patterns of change in hand deformity over time were identified. It is recommended that children with cerebral palsy involving their upper limbs be monitored regularly. Significance of the study: This is the first study to document longitudinal changes in hand deformity in children with cerebral palsy.